(untitled) (Politeja, 2025)
“WHAT IS SOCIAL”… TOWARDS CONTEMPORARY CIVILIZATION THREATS The topic of consideration is the analysis of a set of concepts developed by Bruno Latour (1947-2022) – a French anthropologist, sociologist and philosopher of science, which – according to the mentioned researcher – can replace the strict distinction between what is technological and what is social. The aim of the considerations is to answer the question whether the concepts proposed by the author of After Lockdown: A Metamorphosis: ‘association’, ‘substitution’ and ‘translation’ – really allow us to go beyond the opposition: social versus technological? Is it possible to reformulate traditional statements regarding social order, power, domination, and therefore also potential threats to civilization? Methodology: analysis of scientific and media discourse.